Los cuentos de Shakespeare - Lamb, Charles 1775-1834; Lamb, Mary 1764-1847 (Ediciones Castillo, 2015)
Retellings of eleven of Shakespeare's best known plays, using the playwright's own words whenever possible
Keywords: Shakespeare, William / 1564-1616 / Stories, plots, etc; Shakespeare, William / 1564-1616 / Adaptations; Shakespeare, William <1564-1616> -- Adaptations; Shakespeare, William -- 1564-1616; Drama; Jugendbuch; Anthologie; Fiktionale Darstellung